Dislocation description of twins in high-temperature superconductor YBa2Cu3O7-d - Boyko, V.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
The thin twins theory consistently applied to the dislocation description of twins in the high-temperature superconductor YBa2Cu3O7-d (YBCO). Quantitative analysis of the twin shape shows an agreement with theoretical consideration and gives new method to evaluate the twin boundary energy gtw. Friction stress Sfr acting on a twinning dislocation is also determined. The formation of a twin and twin microstructures are analyzed. The principles of microstructure design by twinning in YBCO crystals for enhanced Jc at high magnetic fields are discussed.